Welcome all to Season 2 of the Brilliant Inequality Contest. Like the Brilliant Integration Contest, the aim of the Inequality Contest is to improve skills and techniques often used in Olympiad-style Inequality problems. But above all, the main reason is so we can have fun.

Anyone is allowed to participate, as long as they adhere to the following rules.

I will post the first problem. If someone solves it, he or she can post a solution and then must post a new problem.

A solution must be posted below the thread of the problem. Then, the solver must post a new problem as a separate thread.

Please make a substantial comment. Spam or unrelated comments will be deleted. (To help me out, try to delete your comments within an hour of when you posted them if they are not the solutions.)

Make sure you know how to solve your own problem before posting it, in case no one else is able to solve it within 48 hours. Then, you must post the solution and you have the right to post a new problem.

If the one who solves the last problem does not post a new problem in 24 hours, the creator of the previous problem has the right to post another problem.

The scope of the problems is Olympiad-style inequalities, but non-standard inequalities are also allowed, (due to increasing number of non-standard inequalities found in olympiads)

You are not allowed to post problems requiring calculus in the solutions (use of differentiation to prove a curve is concave or convex is allowed).

Lagrange Multipliers are not allowed to be used in a solution.

Most Standard Inequalities are allowed to be used, including AM-GM, Muirhead, Power Mean and Weighted Power Mean, Cauchy-Schwarz, Holder, Rearrangement, Chebyshev, Schur, Jensen, Karamata, Reverse Rearrangement, Bernoulli's Inequality and Titu's lemma.

Try to post the simplest solution possible. For example, if someone posted a solution using Holder, Titu's and Cauchy, when there is a solution using only AM-GM, the latter is preferred.

Format your proof as follows:

SOLUTION OF PROBLEM(insert problem number here)

[Post your solution here]

PROBLEM(insert problem number here)

[Post your problem here]

Remember to reshare this note so it goes to everyone out there. Also remember to keep the comments sorted by Newest, so you can see the current problem. And above all else, have fun!!!

PROBLEM 1For real numbers \(a_1, a_2, \ldots\), if \(a_{n-1} + a_{n+1} \geq 2a_n\) for \(n\geq 2\), then prove that

\[A_{n-1} + A_{n+1} \geq 2A_n \quad \text{ for } n\geq 2.\]

where \(A_n\) is the average of \(a_1, a_2, \ldots, a_n\).

No vote yet

1 vote

×

Problem Loading...

Note Loading...

Set Loading...

Easy Math Editor

`*italics*`

or`_italics_`

italics`**bold**`

or`__bold__`

boldNote: you must add a full line of space before and after lists for them to show up correctlyparagraph 1

paragraph 2

`[example link](https://brilliant.org)`

`> This is a quote`

Remember to wrap math in \( ... \) or \[ ... \] to ensure proper formatting.`2 \times 3`

`2^{34}`

`a_{i-1}`

`\frac{2}{3}`

`\sqrt{2}`

`\sum_{i=1}^3`

`\sin \theta`

`\boxed{123}`

## Comments

Sort by:

TopNewestProblem 6:Let \(a\), \(b\) and \(c\) be positive reals such that \(abc=1\). Prove that: \[1+\sqrt[3]{(a^3+1)(b^3+1)(c^3+1)}\ge\dfrac{1}{a}+\dfrac{1}{b}+\dfrac{1}{c}\]

Log in to reply

Solution:\[\begin{align} 1+\sqrt[3]{(a^3+1)(b^3+1)(c^3+1)} &\geq \dfrac{a}{b} + \dfrac {b}{c} + \dfrac {c}{a}\\ (a^3+1)(b^3+1)(c^3+1) &\geq (ab+bc+ca-1)^3\\ \displaystyle \sum_{\text{cyc}} a^3 + 3 \displaystyle \sum_{\text{cyc}} a^2 b^2 + 6 \displaystyle \sum_{\text{cyc}} a^2 bc &\geq 3 \displaystyle \sum_{\text{sym}} a^2 b + 3 \displaystyle \sum_{\text{cyc}} ab + 3 \end{align}\]

The rest is just homogenisation and Muirhead bashing, which I'll update later since I have to go.

Log in to reply

Can you update your complete solution?

Log in to reply

Problem 4Prove that for all non-negative real numbers \(x,y,z\),

\[6(x+y-z)(x^2+y^2+z^2)+27xyz \le 10(x^2+y^2+z^2)^{3/2}\]

Log in to reply

Applying Cauchy-Schwarz inequality, we have:

\(\quad (x^2+y^2+z^2)(2^2+2^2+1^2)\ge(2x+2y+z)^2\)

or \(3(x^2+y^2+z^2)^{1/2}\ge 2x+2y+z\).

Hence,

\(\quad10(x^2+y^2+z^2)^{3/2}-6(x+y-z)(x^2+y^2+z^2)\)

\(\ge(x^2+y^2+z^2)\left(\dfrac{10}{3}(2x+2y+z)-6(x+y-z)\right)\)

\(=\dfrac{1}{3}(x^2+y^2+z^2)(2x+2y+28z)\)

Appying AM-GM inequality, we have:

\(x^2+y^2+z^2=4\cdot\dfrac{x^2}{4}+4\cdot\dfrac{y^2}{4}+z^2\ge9\sqrt[9]{\dfrac{x^8y^8z^2}{4^8}}\)

\(2x+2y+28z=2x+2y+7\cdot 4z\ge 9\sqrt[9]{2x\cdot2y\cdot(4z)^7}=9\sqrt[9]{4^8xyz^7}\)

This implies that \((x^2+y^2+z^2)(2x+2y+28z)\ge 81xyz\), we are done.

The equality holds if and only if \(x=y=2z\).

Log in to reply

Problem 12:Let \(a,b\) and \(c\) be real numbers such that: \(-1\le a,b,c\le 1\) and \(a+b+c=0\).

Prove that: \(a^2+b^4+c^6\le 2\).

Log in to reply

Can you post your solution?

I'm not sure whether this hould keep running, due to lack of participants. Thoughts?

Log in to reply

Sorry for late reply. In a recent days, my family and I are welcoming the Vietnamese New Year.

This is the solution:

Because \(a^2+b^4+c^6\le a^2+b^2+c^2\), we can prove a stronger inequality: \(a^2+b^2+c^2\le 2\).

WLOG, assume that \(a\le b\le c\). hence \(-1\le a\le 0\le c\le 1\).

We have: \(a(a+1)\le 0\) or \(a^2\le -a\); \(c(c-1)\le 0\) or \(c^2\le c\).

If \(-1\le b\le 0\), we get \(b^2\le -b\), so \(a^2+b^2+c^2\le -a-b+c=2c\le 2\).

If \(0\le b\le 1\), we get \(b^2\le b\), so \(a^2+b^2+c^2\le -a+b+c=-2a\le 2\).

Equility holds when \((a,b,c)=(-1,0,1)\) and its permutations.

Log in to reply

Sharky, is the rules number 9 are all the inequality formula that have been discovered ?

I'm just here to try problem and study XD

Even though i didn't solve one of them

Log in to reply

Log in to reply

Problem 11:Let \(a,b\) and \(c\) be positive reals such that \(a+b+c=1\). Prove that: \[\sqrt{a+\dfrac{(b-c)^2}{4}}+\sqrt b+\sqrt c\le\sqrt3\]

Log in to reply

Can you please write your solution? The time has passed.

Log in to reply

Applying the Cauchy-Schwarz inequality, we have:

\(\quad\left(\sqrt{a+\dfrac{(b-c)^2}{4}}+\sqrt b+\sqrt c\right)^2\)

\(\le 3\left[a+\dfrac{(b-c)^2}{4}+\dfrac{\left(\sqrt b+\sqrt c\right)^2}{4}+\dfrac{\left(\sqrt b+\sqrt c\right)^2}{4}\right]\)

\(=3\left[a+\dfrac{(b-c)^2+2(b+c)+4\sqrt{bc}}{4}\right]\)

\(=3\left[a+\dfrac{2(b+c)+\left(\sqrt b+\sqrt c\right)^2\left(\sqrt b-\sqrt c\right)^2+4\sqrt{bc}}{4}\right]\)

\(\le 3\left[a+\dfrac{2(b+c)+2(b+c)\left(\sqrt b-\sqrt c\right)^2+4\sqrt{bc}}{4}\right]\)

\(\le 3\left[a+\dfrac{2(b+c)+2\left(\sqrt b-\sqrt c\right)^2+4\sqrt{bc}}{4}\right]\)

\(\le 3\left[a+\dfrac{2(b+c)+2(b+c)}{4}\right]=3\), Q.E.D.

The equality occurs iff \(a=b=c=\dfrac{1}{3}\).

Log in to reply

Log in to reply

Problem 10:Let \(a,b,c,d,e\) be non-negative real numbers such that \(a+b+c+d+e=5\). Prove that: \[abc+bcd+cde+dea+eab\le5\]

Log in to reply

Solution:Assume \(e=\min\{a, b, c, d,e\}\). Then AM-GM gives :

\(e(c + a)(b + d) + bc(a + d − e) \le \dfrac{e(5 − e)^2}{4}+\dfrac{(5 − 2e)^2}{27}\le 5\)

the last one being equivalent with: \((e − 1)^2(e + 8)\ge 0\), which is true.

Log in to reply

Problem 9:For \(0 \leq a \leq b \leq c \leq d \leq e\) and \(a+b+c+d+e=1\), show that

\[ad + dc + cb + be +ea \leq \dfrac {1}{5}\]

Log in to reply

Solution:Since, \(a\le b\le c\le d\le e\), we get \(a+b\le a+c\le b+d\le c+e\le d+e\).

Applying the Chebyshev's inequality, we have:

\(\quad2(a+b+c+d+e)^2\)

\(=\left(a+b+c+d+e\right)\left((d+e)+(c+e)+(b+d)+(a+c)+(a+b)\right)\)

\(\ge 5(ad+ae+bc+be+cb+cd+da+dc+ea+eb)\)

\(=10(ad+dc+cb+be+ea)\)

Hence, \(ad+dc+cb+be+ea\le\dfrac{1}{5}(a+b+c+d+e)^2=\dfrac{1}{5}\).

The equality holds when \(a=b=c=d=e=\dfrac{1}{5}\).

Log in to reply

Problem 8:Let \(a_1 \geq a_2 \geq \ldots \geq a_n \geq a_{n+1} = 0\) be a sequence of real numbers. Prove that

\[\sqrt {\displaystyle \sum_{k=1}^n a_{k}} \leq \displaystyle \sum_{k=1}^n \sqrt{k} (\sqrt{a_k} - \sqrt{a_{k+1}})\]

Log in to reply

Solution:Sorry for the late reply.

Let \(x_k = \sqrt{a_k} - \sqrt{a_{k+1}}\). Then, \(a_k = (x_k + x_{k+1} + \ldots + x_{n})^2\). Thus,

\[\begin{align} \displaystyle \sum_{k=1}^n &= \displaystyle \sum_{k=1}^n (x_k + x_{k+1} + \ldots + x_n)^2 = \displaystyle \sum_{k=1}^n kx_k^2 + 2 \displaystyle \sum_{1 \leq i \leq j \leq n} i x_i x_j\\ &\leq \displaystyle \sum_{k=1}^n kx_k^2 + 2\displaystyle \sum_{1\leq i \leq j \leq n} \sqrt{ij}x_i x_j = \left ( \displaystyle \sum_{k=1}^n \sqrt{k} x_k \right ) ^2\\ \end{align}\]

Taking the square root of both sides gives us the desired inequality.

Log in to reply

Problem 7:Given distinct positive integers \(a_1, a_2, \ldots, a_n\), prove that

\[(a_1^7 + a_2^7 + \ldots + a_n^7) + (a_1^5 + a_2^5 + \ldots + a_n^5) \geq 2(a_1^3 + a_2^3 + \ldots + a_n^3)^2\]

Also, find the equality case.

Log in to reply

Solution:We try to prove this via induction.

For \(n=1\), we have

\[a_1^7 + a_1^5 - 2(a_1^3)^2 = a_1^5 (a_1-1)^2 \geq 0\]

so the base case \(n=1\) is true. Suppose the case is true for \(n=k\). For the case \(n=k+1\), we first WLOG \(a_1 < a_2 < \ldots < a_{k+1}\). We have

\[\begin{align} 2(a_1^3+a_2^3+\ldots + a_{k+1}^3)^2 - 2(a_1^3+a_2^3+\ldots + a_k^3)^2 &= 2a_{k+1}^6 + 4a_{k+1}^3 (a_1^3 + \ldots + a_k^3)\\ & \leq 2a_{k+1}^6 + 4a_{k+1}^3 (1^3 + 2^3 + \ldots + (a_{k+1}-1)^3)\\ &= 2a_{k+1}^6 + 4a_{k+1}^3 \dfrac{(a_{k+1}-1)^2 a_{k+1}^2}{4}\\ &= a_{k+1}^7 + a_{k+1}^5\\ \end{align}\]

Thus, \((a_1^7 + a_2^7 + \ldots + a_n^7) + (a_1^5 + a_2^5 + \ldots + a_n^5) \geq 2(a_1^3 + a_2^3 + \ldots + a_n^3)^2\), with equality iff \(a_1 =1, a_2 = 2, \ldots, a_n = n\).

Log in to reply

Problem 5:Let \(a,b,c\) be

realnumbers such that \(a+b+c=0\).Prove that:

\[a^2b^2+b^2c^2+c^2a^2+6abc+3\ge0\]

Log in to reply

48 hours have passed since I posted this problem. Here is a solution.

WLOG, assume that \(ab\ge 0\).

From \(a+b+c=0\), we have \(c=-(a+b)\).

Substituiting this in to the inequation we wish to prove, we have:

\(\quad (a^2+b^2)(a+b)^2+a^2b^2-6ab(a+b)+3\ge0\)

or \((a^2+ab+b^2)^2-6ab(a+b)+3\ge 0\).

Appying AM-GM inequality, we have:

\(\quad (a^2+ab+b^2)^2-6ab(a+b)+3\)

\(\ge \dfrac{(a^2+ab+b^2)^2}{3}+\dfrac{2(a^2+ab+b^2)^2}{3}-\dfrac{3ab[(a+b)^2+4]}{2}+3\)

\(\ge \dfrac{9a^2b^2}{3}+2ab(a^2+ab+b^2)-\dfrac{3ab(a+b)^2}{2}-6ab+3\)

\(=3(ab-1)^2+\dfrac{ab(a-b)^2}{2}\ge0\).

We have equality for \((a,b,c)=(1,1,-2)\) and its permutations.

Log in to reply

Problem 3Let \(a\), \(b\) and \(c\) be positive reals such that \(abc \leq 1\). Prove that

\[\dfrac {a}{c} + \dfrac {b}{a} + \dfrac {c}{b} \geq a + b + c\]

Log in to reply

By AM-GM inequality,

\(\dfrac{a}{b}+\dfrac{c}{a}+\dfrac{c}{a} \ge 3 \sqrt[3]{\frac{c^2}{ab}} \ge 3 \sqrt[3]{c^3} = 3c\)

Similarly, \(\dfrac{b}{c}+\dfrac{a}{b}+\dfrac{a}{b} \ge 3 \sqrt[3]{\frac{a^2}{bc}} \ge 3 \sqrt[3]{a^3} = 3a\)

and \(\dfrac{c}{a}+\dfrac{b}{c}+\dfrac{b}{c} \ge 3 \sqrt[3]{\frac{b^2}{ca}} \ge 3 \sqrt[3]{b^3} = 3b\)

Adding all the equaions, \(3 \left(\dfrac{a}{b} + \dfrac{b}{c} + \dfrac{c}{a} \right) \ge 3(a+b+c)\).

Hence, \(\dfrac{a}{b} + \dfrac{b}{c} + \dfrac{c}{a} \ge a+b+c\) with equality iff \(a=b=c=1\).

Log in to reply

\( \large 2^{nd} ques \) \[\] if a,b,c are the sides of a triangle provided with perimeter of this triangle i.e 10 \[\] \( \large Prove\ that : \) \[\] \( \large { a }^{ 2 }+{ b }^{ 2 }+{ c }^{ 2 }+\frac { 2 }{ 5 } abc\quad <\quad 50 \)

Log in to reply

Solution to Problem 2Let \(a=x+y\), \(b=y+z\), \(c=z+x\). Since \(a\), \(b\) and \(c\) are sides of a triangle, \(x\), \(y\) and \(z\) must be positive by incentre properties. Also, since \(a+b+c=10\), \(x+y+z=5\). Substituiting this in to the inequation we wish to prove, we have:

\[\begin{align} (x+y)^2 + (y+z)^2 + (z+x)^2 + \dfrac{2}{5} (x+y)(y+z)(z+x) &< 50\\ 5x^2 + 5y^2 + 5z^2 + 5xy + 5yz + 5zx + x^2 y + x^2 z + y^2 x + y^2 z + z^2 x + z^2 y + 2xyz &< 125\\ (x+y+z)(x^2 + y^2 + z^2 + xy + yz + zx) + x^2 y + x^2 z + y^2 x + y^2 z + z^2 x + z^2 y + 2xyz &< (x+y+z)^3\\ x^3 + y^3 + z^3 + 3(x^2 y + x^2 z + y^2 x + y^2 z + z^2 x + z^2 y) + 5xyz &< x^3 + y^3 + z^3 + 3(x^2 y + x^2 z + y^2 x + y^2 z + z^2 x + z^2 y) + 6xyz\\ 0 &< xyz\\ \end{align}\]

We have already said that \(x\), \(y\) and \(z\) are positive, so the final expression is obviously true. Therefore, the first expression must be true. Thus, proven.

For further details, what I have done is use the incircle substitution so I can get rid of the weird triangle condition. Since every triangle has an incircle, and tangents to a circle from a point are equal, we can use this substitution.

In the second half of my proof, I homogenised all the terms by substituting \(x+y+z=5\) so they were all degree 3, and they simplified down to the final expression.

Log in to reply

Yeah Ravi substitution is best when dealing with triangle sides inequalities !

Log in to reply

let us change first n-1 -> let's say z then \( a_{z} \) + \( a_{z+2} \) >= 2 \( a _{z+1} \) , now \( A_{n} \) = \( a_{1} \) ...........+ \( a_{z} \) if we repeatedly add the given condition in the question i.e. \( a_{z} \) + \( a_{z+2} \) >= 2 \( a _{z+1} \) you may refer to these pics but the handwriting is very poor :P!

Log in to reply

For anyone interested in my proof of this problem, the algebra bash is fairly straightforward (clear out denominators, subtract and add, but be careful not to make errors). We manipulate \(A_{n-1} + A_{n+1} \geq 2A_{n}\) to

\[a_{1} + a_{2} + \ldots + a_{n-1} - \dfrac {n^2+n-2}{2} a_n + \dfrac {n(n-1)}{2} a_{n+1} \geq 0\]

However, we can convert this into the telescoping sum

\[=\displaystyle \sum_{k=2}^n \dfrac{k(k-1)}{2}(a_{k-1} - 2a_{k} + a_{k+1}) \geq 0\]

The final expression is true by our original condition, so we are done.

Log in to reply

yes, good one !

Log in to reply

You have quite a few typos, but the essence of the proof is there, so I think you have solved it. I would recommend just going over the proof and fixing up the small errors you made to make it better. Good job. :)

Log in to reply